Development of Disciplinary Behavior in Civics at SD Negeri 15 Koto Lalang - Mai Sri Lena; Sahrun Nisa; Fitri Oriza Sativa Hani; Sanseni Safitri (Formosa Journal of Applied Sciences, 2023)
This study has objectives which include (1) providing a description of Civics Learning planning in the formation of student discipline behavior; (2) compiling a program to develop student discipline behavior; and (3) evaluating the development of students' disciplinary behavior. The approach and type of research used in this research is descriptive qualitative. The informants who were the source of the research data were the deputy principal, teachers, and students from SD Negeri 15 Koto Lalang. The results of the study show that at the planning stage, the teacher plans the development of disciplinary behavior by integrating this behavior into the assessment stage carried out by the teacher using a behavior development diary and observation sheets of student behavior during the learning process. From the results of the study, it can be concluded that undisciplined student behavior is seen in routine activities such as queuing and doing assignments given by the teacher.